Highly regioselective synthesis of chiral diamines via a Buchwald–Hartwig amination from camphoric acid and their application in the Henry reaction. (29th May 2014) - Uzarewicz‐Baig, Magdalena; Koppenwallner, Maximilian; Tabassum, Sobia; Wilhelm, René
<x xml:space="preserve">Abstract</x> In this work the synthesis of new asymmetric diamine ligands from camphoric acid is described. The new diamines can be directly prepared in a regioselective arylation of the less hindered primary amine group of (+)‐cis‐1, 2, 2‐trimethylcyclopentane‐1, 3‐diamine via a Buchwald–Hartwig amination in high yields. The resulting diamines incorporate a secondary and primary amine group and were successfully applied as ligands in a copper‐catalyzed Henry reaction. Copyright © 2014 John Wiley & Sons, Ltd.